Cooperative game theory based load balancing in long term evolution network - Saha, Subarno; Hossain, Rajkin; Khan, Muhidul Islam (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 1st International Conference on Computer and Information Engineering, ICCIE 2015; Department of Computer Science and Engineering (CSE) of Rajshahi University of Engineering and Technology (RUET)Rajshahi; Bangladesh; 26 November 2015 through 27 November 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/CCIE.2015.7399302